Techno-economic analysis for brewer’s spent grains use on a biorefinery concept: The Brazilian case - Mussatto, Solange I. (2013)
A techno-economic analysis for use of brewer’s spent grains (BSG) on a biorefinery concept for the Brazilian case is presented. Four scenarios based on different levels of heat and mass integration for the production of xylitol, lactic acid, activated carbon and phenolic acids are shown. A simulation procedure using the software Aspen Plus and experimental yields was used. Such procedure served as basis for the techno-economic and environmental assessment according to the Brazilian conditions. Full mass integration on water and full energy integration was the configuration with the best economic and environmental performance. For this case, the obtained economic margin was 62.25%, the potential environmental impact was 0.012 PEI/kg products, and the carbon footprint of the processing stage represented 0.96 kg CO2-e/kg of BSG. This result served as basis to draw recommendations on the technological, economic and environmental feasibility for implementation of such type of biorefinery in Brazil.